The role of PKCε-dependent signaling for cardiac differentiation - Galli, D.; Gobbi, G.; Carrubbi, C.; Di Marcantonio, D.; Benedetti, L.; De Angelis, M.; Meschi, T.; Vaccarezza, Mauro; Sampaolesi, M.; Mirandola, P.; Vitale, M. (2013)
Protein kinase Cepsilon (PKCε) exerts a well-known cardio-protective activity in ischemia–reperfusion injury and plays a pivotal role in stem cell proliferation and differentiation. Although many studies have been performed on physiological and morphological effects of PKCε mis-expression in cardiomyocytes, molecular information on the role of PKCε on early cardiac gene expression are still lacking. We addressed the molecular role of PKCε in cardiac cells using mouse cardiomyocytes and rat bone marrow mesenchymal stem cells. We show that PKCε is modulated in cardiac differentiation producing an opposite regulation of the cardiac genes NK2 transcription factor related, locus 5 (nkx2.5) and GATA binding protein 4 (gata4) both in vivo and in vitro. Phospho-extracellular regulated mitogen-activated protein kinase 1/2 (p-ERK1/2) levels increase in PKCε over-expressing cells, while pkcε siRNAs produce a decrease in p-ERK1/2. Indeed, pharmacological inhibition of ERK1/2 rescues the expression levels of both nkx2.5 and gata4, suggesting that a reinforced (mitogen-activated protein kinase) MAPK signaling is at the basis of the observed inhibition of cardiac gene expression in the PKCε over-expressing hearts. We demonstrate that PKCε is critical for cardiac cell early gene expression evidencing that this protein is a regulator that has to be fine tuned in precursor cardiac cells.